Bone Marrow Mesenchymal Stem Cell-Derived Exosome-Educated Macrophages Promote Functional Healing After Spinal Cord Injury - Li, Chengjun; Qin, Tian; Zhao, Jinyun; He, Rundong; Wen, Haicheng; Duan, Chunyue; Lu, Hongbin; Cao, Yong; Hu, Jianzhong (Frontiers in Cellular Neuroscience, 2021)
The spinal cord injury is a site of severe central nervous system (CNS) trauma and disease without an effective treatment strategy. Neurovascular injuries occur spontaneously following spinal cord injury (SCI), leading to irreversible loss of motor and sensory function. Bone marrow mesenchymal stem cell (BMSC)–derived exosome-educated macrophages (EEM) have great characteristics as therapeutic candidates for SCI treatment. It remains unknown whether EEM could promote functional healing after SCI. The effect of EEM on neurovascular regeneration after SCI needs to be further explored. We generated M2-like macrophages using exosomes isolated from BMSCs, which were known as EEM, and directly used these EEM for SCI treatment. We aimed to investigate the effects of EEM using a spinal cord contusive injury mouse model in vivo combined with an in vitro cell functional assay and compared the results to those of a normal spinal cord without any biological intervention, or PBS treatment or macrophage alone (MQ). Neurological function measurements and histochemical tests were performed to evaluate the effect of EEM on angiogenesis and axon regrowth. In the current study, we found that treatment with EEM effectively promoted the angiogenic activity of HUVECs and axonal growth in cortical neurons. Furthermore, exogenous administration of EEM directly into the injured spinal cord could promote neurological functional healing by modulating angiogenesis and axon growth. EEM treatment could provide a novel strategy to promote healing after SCI and various other neurovascular injury disorders.